Preliminary evidences of arrested development of gastro-intestinal nematodes of zebu calves reared extensively in a savannah area of the state of Mato Grosso, Brazil - Melo, Hermano J.H. de (Pesquisa Agropecuaria Brasileira, 2014)
Preliminary studies were carried out to seek evidences for arrested development of gastrointestinal nematodes of calves reared extensively during the dry period in a Savannah area of Mato Grosso State, Brazil. Necropsy findings of two groups of calves slaughtered respectively at the begginning and the peak of the dry period, showed that number of arrested forms increased, relative to the number of adult worms, as the dry season advanced. Mean faecal egg counts of one group of Zebu calves treated on two occasions with a broad spectrum anthelmintis increased within intervals of fourteen days after each treatment. This period of time is less than the minimal prepatent periods for gastrointestinal nematodes of cattle. These results are indicative that some arrested development of Cooperia spp. (C. punctata e C. pectinata) and Haemonchus spp. (H. similis and H. contortus) may occur during the dry winter periods in the Savannah area of Mato Grosso, Brazil.